Public art in Canada : critical perspectives - Gérin, Annie, 1969-; McLean, James S., 1956- (University of Toronto Press, 2009)
The rigorous essays and original works of art collected in this volume present a compelling demonstration of the strategies, aesthetic and otherwise, used by artists to elicit intellectual, sensual, or emotional responses that can only be obtained through artistic practices in public places.